Formulation and evaluation of antimicrobial gel of cow urine distillate (Journal of Basic and Applied Research in Biomedicine, 2022)
In India, medicines based on herbal origin have been the basis of treatment and cure for various diseases. The Indian Cow, Bos indicus, is a most veneered and valuable animal in religious scriptures. Cow urine has found therapeutic applications since days of yore. Cow urine based preparations have powerful antimicrobial, antiviral, anti allergic, and antioxidant activity. So the current research is mainly centered on the exploration of the antimicrobial powers of cow urine and incorporation of cow urine into gel formulation. The gels were prepared by using carbopol 940, propylene glycol, glycerin, triethanolamine, distilled water along with cow urine distillate and Azadirachta indica extract. The prepared gels were evaluated for physical appearance, spreadability, pH, Homogeneity and viscosity. The present study analyzes the antibacterial and antifungal activity of Cow Urine Distillate against the clinical pathogenic microorganisms such as Bacillus subtilis and Staphalococcus aureus. Maximum antibacterial activity was observed in Bacillus subtilis than Staphalococcus aureus. Antifungal activity of cow urine distillate was analysed against Aspergillus niger. The result revealed optimum characteristics features of gel formulation and confirm antimicrobial potential of prepared gel.